Are we ready for the revision of the 14-day rule? Implications from Chinese legislations guiding human embryo and embryoid research - Xue, Yang; Shang, Lijun (Frontiers in Cell and Developmental Biology, 2022)
The ISSCR recently released new guidelines that relaxed the 14-day rule taking away the tough barrier, and this has rekindled relevant ethical controversies and posed a fresh set of challenges to each nation’s legislations and policies directly or indirectly. To understand its broad implications and the variation and impact of China’s relevant national policies, we reviewed and evaluated Chinese laws, administrative regulations, departmental rules, and normative documents on fundamental and preclinical research involving human embryos from 1985 to 2022 in this paper. We have historically examined whether these regulations, including a 14-day rule, had restrictions on human embryo research, and whether and how these policies affected human embryo and embryoid research in China. We also discussed and assessed the backdrop in which China has endeavored to handle such as the need for expanding debates among justice practice, academia, and the public, and the shifting external environment influenced by fast-developing science and technology and people’s culture and religions. In general, Chinese society commonly opposes giving embryos or fetuses the legal status of humans, presumably due to the Chinese public not seeming to have any strong religious beliefs regarding the embryo. On this basis, they do not strongly oppose the potential expansion of the 14-day rule. After the guidelines to strengthen governance over ethics in science, and technology were released by the Chinese government in 2022, Chinese policymakers have incorporated bioethics into the national strategic goals using a “People-Centered” approach to develop and promote an ecological civilization. Specifically, China follows the “precautionary principle” based on ethical priority as it believes that if scientific research carries any potential technological and moral risks on which no social ethical consensus has been attained, there would be a need to impose oversight for prevention and precaution. At the same time, China has adopted a hybrid legislative model of legislation and ethical regulations with criminal, civil and administrative sanctions and a 14-day limit specified within its national hESCs guidelines. This would certainly be a useful example for other countries to use when considering the possibility of developing a comprehensive, credible and sustainable regulatory framework.